2012
DOI: 10.1161/hypertensionaha.112.195891
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism Can Be Useful in the Identification of Primary Aldosteronism Due To Aldosterone-Producing Adenoma

Abstract: Abstract-Hyperparathyroidism represents as a novel feature of primary aldosteronism (PA). Its occurrence in patients with the surgically correctable aldosterone-producing adenoma (APA) and not in those with bilateral adrenal hyperplasia suggested that the measurement of parathyroid hormone could help in differentiating between these subtypes of PA. To test this hypothesis we measured the plasma levels of intact parathyroid hormone, Ca 2ϩ , and several markers of calcium/phosphorus metabolism in 132 hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…In 1 study, serum 18OHB, 18-hydroxycortisol, and 18-oxocortisol before and after saline infusion were all higher in patients with APA than those with IHA or essential hypertension 70 ; likewise, the serum levels of parathyroid hormone and of autoantibodies for the type 1 angiotensin receptor were all higher in patients with APA than those with IHA or essential hypertension, with only small overlap between values for patients with APA and IHA. 71,72 Consequently, peripheral blood values for these substances, in combination with clinical criteria such as hypokalemia or lack thereof, 18,49 might be used to characterize which patients will benefit most from AVS when access to AVS and resources are limited.…”
Section: Clinical Decision Making Based On Equivocal Avs Resultsmentioning
confidence: 99%
“…In 1 study, serum 18OHB, 18-hydroxycortisol, and 18-oxocortisol before and after saline infusion were all higher in patients with APA than those with IHA or essential hypertension 70 ; likewise, the serum levels of parathyroid hormone and of autoantibodies for the type 1 angiotensin receptor were all higher in patients with APA than those with IHA or essential hypertension, with only small overlap between values for patients with APA and IHA. 71,72 Consequently, peripheral blood values for these substances, in combination with clinical criteria such as hypokalemia or lack thereof, 18,49 might be used to characterize which patients will benefit most from AVS when access to AVS and resources are limited.…”
Section: Clinical Decision Making Based On Equivocal Avs Resultsmentioning
confidence: 99%
“…27,28 Likewise, the recently reported increase of parathyroid hormone in PA patients was found in APA patients and not IHA patients, 29,30 thus being clinically helpful in the differential diagnosis between these conditions. 31 Furthermore, Satoh et al recently reported that 18-OH cortisol and 18-oxo cortisol were raised in patients with APA, and not in those with IHA. 32 Hence, the present result is not unique in showing biomarker differences between the APA and IHA patients.…”
Section: Discussionmentioning
confidence: 98%
“…Another recent study from our group showed that patients with APA have a 31 % higher parathormone (PTH) levels than demographically comparable primary (essential) hypertension patients with similarly elevated blood pressure values [ 52 ]. A mild increase of PTH can therefore be a further, albeit hitherto unappreciated, feature of APA that can be useful in pinpointing the patients with these tumors [ 52 ].…”
Section: Molecular Mechanisms Of Pamentioning
confidence: 94%